2007
DOI: 10.1176/ps.2007.58.9.1219
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision-Making Preferences of People With Severe Mental Illness

Abstract: Most clients with severe mental illnesses prefer shared decision making, particularly in relation to their mental health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
104
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(111 citation statements)
references
References 10 publications
4
104
0
3
Order By: Relevance
“…SDM involves collaborative partnership between patients and providers who are both considered experts and are expected to participate in deliberation about treatment decisions (Charles, Gafni, & Whelan, 1997). Studies in various clinical settings have found that patients prefer SDM (Adams, Drake, & Wolford, 2007;Betinger, Kissling, & Hamann, 2014;Goossensen, Ziilstra & Koopmanschap, 2007;Hamann, Cohen, Leucht, Busch, & Kissling, 2005;Hill & Laugharne, 2005;Matthias, Salyers, Rollins, & Frankel, 2012a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SDM involves collaborative partnership between patients and providers who are both considered experts and are expected to participate in deliberation about treatment decisions (Charles, Gafni, & Whelan, 1997). Studies in various clinical settings have found that patients prefer SDM (Adams, Drake, & Wolford, 2007;Betinger, Kissling, & Hamann, 2014;Goossensen, Ziilstra & Koopmanschap, 2007;Hamann, Cohen, Leucht, Busch, & Kissling, 2005;Hill & Laugharne, 2005;Matthias, Salyers, Rollins, & Frankel, 2012a).…”
mentioning
confidence: 99%
“…While some studies have examined SDM in outpatient mental health settings (Adams, Drake, & Wolford, 2007;De Las Cuevas, Penate, Perestelo-Perez, & Serrano-Aguilar, 2013;Fukui et al, 2014), few have explored patients' appraisals of how treatment decisions are made in mental health. To better understand patientlevel factors that might influence participation in SDM we examined patients' perceptions of treatment decision-making with mental health providers.…”
mentioning
confidence: 99%
“…La mayor parte de los pacientes psiquiátricos desean participar en la toma de decisiones sanitarias, especialmente sobre la medicación y hospitalización (75)(76)(77)(78)(79)(80) …”
Section: ¿Quieren Los Pacientes Psiquiátricos Estar Implicados En La unclassified
“…Montori and colleagues 43 subsequently added to this conceptual definition of shared decision-making by stating (specific to decision making in health care) that a decision is only shared if there is an ongoing partnership and collaboration between the health care worker and patient. Adams and colleagues 44 emphasise the patient participation angle of shared decision-making, highlighting that patients should have accessible information, enabling them to participate in an active and meaningful way.…”
Section: Introductionmentioning
confidence: 99%